Pengabdian Pengabdian Milenial Cerdas Bisnis dan Keuangan - Reviandani, Wasti; Aslamiyah, Suaibatul (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2024)
The millennial generation is currently known as a generation that is close to technological developments, easy to get along with and often uses social media. The millennial generation often has a fairly luxurious lifestyle, such as traveling, eating, drinking coffee or dressing and using the latest smartphones and much more. In the business world, technology can help manage business, make business more efficient, simplify business, and make business easier for traders and customers. Millennials are also more open-minded, because they easily get information from different environments and sources to open up different perspectives. This ability is able to produce ideas and business plans that are more creative, unpredictable and can provide more solutions to society. Millennials can also take risks with their actions, but be careful. The aim of the service is to explain in more detail about the business that can be done and its development as well as financial management participants can understand how to start a simple business and understand how towhich must be started early. Socialization was carried out face to face with students and teachers at Muhammadiyah Cerme Gresik High School. Simultaneously with presenting the material, the implementing team broadcast videos that had been made by the implementing team on YouTube regarding business activities and basic financial management. The final result is that separate personal finances from business finances.